Neutrophil-to-Hemoglobin Ratio and Monocyte-to-Hemoglobin Ratio Predict Prolonged Length of Stay in Patients Undergoing Surgery for Pelvic or Acetabular Fractures - Wei-Gang Pan; Yu-Ching Chou; Tsu-Te Yeh (Journal of Investigative Surgery)
Objective This study evaluated the neutrophil-to-hemoglobin ratio (NHR) and monocyte-to-hemoglobin ratio (MHR) as predictors of prolonged hospital stay in patients undergoing surgery for pelvic or acetabular fractures.Methods We retrospectively reviewed records of patients aged ≥ 18 years who underwent open reduction and internal fixation (ORIF). NHR and MHR were calculated from blood samples at admission and 24 hours postoperatively. Prolonged hospital length of stay (LOS) was defined as ≥ 25 days (75th percentile). Optimal cutoffs were determined by ROC curve analysis. Multivariable logistic regression identified associations between clinical variables and prolonged LOS.Results Among 172 patients (mean age 44.5), postoperative NHR > 0.46 and MHR > 0.02 were independently associated with prolonged LOS in patients with acetabular fractures (aOR = 5.90 and 5.42, respectively). No significant associations were found in pelvic fractures.Conclusions Elevated postoperative NHR and MHR are strongly associated with prolonged LOS in patients with acetabular fractures and may assist in perioperative risk stratification and clinical decision-making.